The Effects of Auditor Change on Audit Fees: Tests of Price Cutting and Price Recovery. - Simon, Daniel T.; Francis, Jere R. (The Accounting Review, 1988)
Abstract The Commission on Auditors' Responsibilities expressed concern for the adverse effect of audit fee price cutting on auditor independence. In the present study, tests were conducted to determine both the presence and magnitude of audit fee price cutting on 1984 audit fees for a sample of 214 firms having changed auditors over the period 1979–1984. A control sample of 226 firms not changing auditors over the same period was used in order to estimate price cutting. Results indicated a significant fee reduction in the initial engagement year that averaged 24 percent of normal fee levels for ongoing engagements, an average fee reduction of 15 percent for each of the next two years, but by the fourth year of the new auditor the fee had increased to normal levels for continuing engagements. The Commission's concern for price cutting's effect on auditor Independence is then reconsidered in the context of recent work on the psychology of sunk costs.